Amplification of homo sapiens CYP2B6 gene using polymerase chain reaction (PCR) for cloning and expression / Norfahmi Mohd Yusof - Mohd Yusof, Norfahmi (2008)
CYP2B6 is a member of cytochrome P450 group of enzymes. The protein encoded by the CYP2B6 gene is the primary metabolizer of a number of drug substrates, such as buprion, cyclosphosphamide, ifosfamide, pethidine, efavirenz, neverapine, ketamine and propofol. In this study, amplification of CYP2B6 gene was performed by using polymerase chain reaction (PCR). The PCR profile for this study was designed in order to amplify the specific CYP2B6 gene sequence. The primers used in this study were designed and analyzed by using computer software called Oligo Analyzer 1.2® and Oligo Explorer 1.2®. The amplification of CYP2B6 was performed by using designed profile in order to amplify the gene of interest. The PCR product was then been purified by centrifugation using Wizard® SV Gel and PCR Clean-Up System.